A new species of the genus Opisthotropis Günther, 1872 (Squamata: Colubridae: Natricinae) from Guangdong Province, China - Yang, Jian-Huan; Sung, Yik-Hei; Chan, Bosco Pui-Lok (Zootaxa, 2013)
A new natricid snake of the genus Opisthotropis Günther, 1872, Opisthotropis laui sp. nov., is described from Mt. Gudou, Jiangmen City, Guangdong Province, China. The new species can be distinguished from other congeners by the combina-tion of the following characters: dorsal scales weakly keeled throughout, in 25:23:23 rows; 10 supralabials; 11 infralabials; two internasals, longer than wide, not touching the loreal; one loreal, not touching the eye; one preocular; two postoculars; one anterior temporal scale; 152 ventrals; 53 subcaudals; body and tail dark olive above, with light yellow crossbars.